Dynamics of Consumer Boycotts: Exploring the Interplay of Expressive and Instrumental Factors - Robertus Suraji; Marrisa Haque; Yasir, Muhammad; Istianingsih, Istianingsih (Dinasti Information and Technology, 2023)
This research explores consumer participation in product boycotts in Indonesia, focusing on the interplay between expressive and instrumental factors over time. Through a systematic literature review, this study reveals that emotional responses and personal identity trigger boycotts, serving as expressions of solidarity or protests against conflicting values. As time progresses, practical considerations, such as boycott effectiveness, become dominant motivators, following the "hot" to "cold" phase transition. Social media plays a critical role in strengthening boycott movements and facilitating discussions that impact this transition. Implications extend to businesses, activists, policymakers, and academics. Companies should develop responsive communication strategies addressing both expressive and instrumental factors. Activists can leverage technology to enhance campaign impact, and policymakers can use insights to encourage responsible business practices. In summary, this research highlights multidimensional boycott dynamics influenced by expressive and instrumental factors, emphasizing the pivotal role of social media and its implications for various stakeholders.